Nested case-control study investigating factors affecting initial adoption of HIV self-testing among men who have sex with men in Guangzhou, China: amidst comprehensive service coverage - Yuzhou Gu; JiaLi Yang; Yefei Luo; Lishan Zhan; Fanghua Liu; Wenting Zeng; Huifang Xu; Huifang Xu; Yongheng Lu; Yanshan Cai; Zhigang Han (Frontiers in Public Health)
BackgroundChina has been exploring HIV self-testing (HIVST) among men who have sex with men (MSM) since 2014. Currently, both non-profit and commercial initiatives HIVST services have achieved comprehensive coverage. Investigating the factors influencing the initial adoption of HIVST among MSM in this context can help develop tailored HIVST service strategies of and further promote HIVST adoption among MSM communities.MethodsWe selected 230 participants from a prospective cohort on HIV infection among MSM population in Guangzhou, China, who had no prior experience of HIVST. Among the study participants, 43 who initially adopted HIVST during the follow-up period were designated as the case group, while the rest comprised the control group. Electronic questionnaires were used for baseline and follow-up surveys to collect demographic information, sexual behavior characteristics and HIVST utilization in the past 6 months. Logistic regression models were applied to analyze the factors influencing the initial adoption of HIVST.ResultsAmong the study participants, 18.7% (43/230) initially adopted HIVST during the follow-up period. Multivariate logistic regression analysis revealed that individuals who primarily sought sexual partners through offline venues in the past 6 months (aOR = 5.28, 95% CI: 1.01–27.79), had more than one sexual partner in the past 6 months (aOR = 2.76, 95% CI: 1.33–5.74), engaged with more than two casual partners in the past 6 months (aOR = 3.02, 95% CI: 1.35–6.78), or had more than one regular partner (aOR = 3.37, 95% CI: 1.51–7.51) exhibited an increased likelihood of initiating HIVST.ConclusionIn the context of comprehensive promotion and coverage of HIVST service, the development of personalized, adaptable, and innovative HIVST strategies for MSM with a higher number of sexual partners, particularly those in regular partnerships and those seeking partners offline, may further increase the adoption of HIVST among MSM.